The Impact of Strategic Marketing Performance on Educational Service Quality and Student Satisfaction: A Case Study of Imam Al-Kadhim College - Abdullah, Ali Ashour (American Journal of Economics and Business Management, 2024)
Strategic marketing performance holds paramount importance in revealing the structural capital of all institutions, particularly educational institutions, amidst the heightened competition witnessed across various sectors. This competition ranges from market saturation of universities and colleges, whether governmental, private, local, or international, to Arab, regional, and global universities. This research aims to elucidate the impact of strategic marketing performance in its dimensions (marketing message, marketing environment, marketing objectives, marketing and strategic planning strategies, human and material resources) on the quality of educational service represented by the following factors (employees, recruitment, faculty members, institutional image (reputation), college infrastructure, educational material, student activities, admissions and registration, library), and student satisfaction represented by dimensions (satisfaction with teaching, administrative, and technical staff, satisfaction with educational material, satisfaction with institutional image (reputation), satisfaction with college infrastructure) for the study sample (Imam Al-Kadhim College) by preparing a questionnaire encompassing three above-mentioned variables and their key inquiries. The results were extracted, confirming the study hypothesis of the significant effect of marketing strategies on the quality of banking service and student satisfaction at Imam Al-Kadhim College.